Interventions to enhance maternal awareness of decreased fetal movement: a systematic review. (2nd December 2015) - Winje, BA; Wojcieszek, AM; Gonzalez‐Angulo, LY; Teoh, Z; Norman, J; Frøen, JF; Flenady, V
Abstract : Background: Decreased fetal movement is associated with adverse pregnancy and birth outcomes; timely reporting and appropriate management may prevent stillbirth. Objectives: Determine effects of interventions to enhance maternal awareness of decreased fetal movement. Search strategy: Cinahl, The Cochrane Library, EMBASE, MEDLINE, PsycINFO and SCOPUS databases; without limitation on language or publication year. Selection criteria: Randomised or non‐randomised studies evaluating interventions to enhance maternal awareness of decreased fetal movement. Data collection and analysis: Two authors independently extracted data and assessed quality. Main results: We included 23 publications from 16 studies of fair to poor quality. We were unable to pool results due to substantial heterogeneity between studies. Three randomised controlled trials (RCTs) and five non‐randomised studies (NRSs), involving 72 888 and 115 435 pregnancies, respectively, assessed effects of interventions on stillbirth and perinatal death. One large cluster RCT ( n  = 68 654) reported no stillbirth reduction, one RCT ( n  = 3111) reported significant stillbirth reduction, and one RCT ( n  = 1123) was small with no deaths. All NRSs favoured intervention over standard care; three studies ( n  = 31 131) reported significant reduction, whereas two studies ( n  = 84 304) reported non‐significant reductions in stillbirth or perinatal deaths. Promising results from NRSs warrant further research. We found no evidence of increased maternal concern following interventions. No cost‐effectiveness data were available. Conclusions: We found no clear evidence of benefit or harm; indirect evidence suggests improved pregnancy and birth outcomes. The optimal approach to support women in monitoring their pregnancies needs to be established. Meanwhile, women need to be informed about the importance of fetal movement for fetal health. Tweetable abstract: The benefits and risks of interventions to increase pregnant women's awareness of fetal movement are unclear. Tweetable abstract: The benefits and risks of interventions to increase pregnant women's awareness of fetal movement are unclear.